Alteration of Extracellular Superoxide Dismutase in Idiopathic Pulmonary Arterial Hypertension - Zhang, Rui; Wang, Lan; Zhao, Qin-Hua; Jiang, Rong; Gong, Su-Gang; Jiang, Xin; Xu, Xi-Qi; He, Yang-Yang; Li, Yuan; Jing, Zhi-Cheng (Frontiers in Medicine, 2020)
Background: Superoxide dismutases (SODs) are an important family of antioxidant enzymes that modulate reactive oxygen species levels. It is largely unknown which SOD isoform(s) change in vivo in idiopathic pulmonary arterial hypertension (IPAH) patients. Methods: A total of 133 consecutive adult IPAH patients who underwent bone morphogenetic protein receptor type 2 (BMPR2) genetic counseling were enrolled in this prospective study. The plasma activities of three subtypes of SOD [copper–zinc (Cu/Zn-SOD), manganese (Mn-SOD), and extracellular SOD (Ec-SOD)] were examined. Results: The activities of SODs were significantly lower in IPAH patients than in healthy subjects. However, only Ec-SOD activity in BMPR2 mutation patients was significantly decreased compared to those in patients without a mutation. The reduced Ec-SOD activity was markedly associated with mean pulmonary arterial pressure, pulmonary vascular resistance (PVR), and 6-min walking distance (6MWD). The reduction of Mn-SOD activity was only associated with 6MWD. There was no association between Cu/Zn-SOD and hemodynamics. Patients with a lower Ec-SOD level had a worse survival compared to those with a higher baseline. The reduced Ec-SOD activity and the raised PVR increased the mortality risk. Conclusions: Ec-SOD was correlated with BMPR2 mutation, hemodynamic dysfunction, and poor outcomes. Circulating Ec-SOD could be a potentially vital antioxidant enzyme in the pathogenesis of IPAH.